Quantitative profiling of the UGT transcriptome in human drug-metabolizing tissues. (2018)
Alternative splicing as a mean to control gene expression and diversify function is suspected to considerably influence drug response and clearance. We report the quantitative expression profiles of the human UGT genes including alternatively spliced variants not previously annotated established by deep RNA-sequencing in tissues of pharmacological importance. We reveal a comprehensive quantification of the alternative UGT transcriptome that differ across tissues and among individuals. Alternative transcripts that comprise novel in-frame sequences associated or not with truncations of the 5'- and/or 3'- termini, significantly contribute to the total expression levels of each UGT1 and UGT2 gene averaging 21% in normal tissues, with expression of UGT2 variants surpassing those of UGT1. Quantitative data expose preferential tissue expression patterns and remodeling in favor of alternative variants upon tumorigenesis. These complex alternative splicing programs have the strong potential to contribute to interindividual variability in drug metabolism in addition to diversify the UGT proteome.